Drug-mediated shortening of action potentials in LQTS2 hiPSC-cardiomyocytes - Duncan, Gary; Firth, Karl S.A.; George, Vinoj; Hoang, Minh Duc; Stainforth, Andrew; Smith, Godfrey; Denning, Chris (Mary Ann Liebert, 2017)
Cardiomyocytes (CMs) derived from human induced pluripotent stem cells (hiPSCs) are now a well-established modality for modeling genetic disorders of the heart. This is especially so for long QT syndrome (LQTS), which is caused by perturbation of ion channel function, and can lead to fainting, malignant arrhythmias and sudden cardiac death. LQTS2 is caused by mutations in KCNH2, a gene whose protein product contributes to IKr (also known as HERG), which is the predominant repolarizing potassium current in CMs. β-blockers are the mainstay treatment for patients with LQTS, functioning by reducing heart rate and arrhythmogenesis. However, they are not effective in around a quarter of LQTS2 patients, in part, because they do not correct the defining feature of the condition, which is excessively prolonged QT interval. Since new therapeutics are needed, in this report, we biopsied skin fibroblasts from a patient who was both genetically and clinically diagnosed with LQTS2. By producing LQTS-hiPSC-CMs, we assessed the impact of different drugs on action potential duration (APD), which is used as an in vitro surrogate for QT interval. Not surprisingly, the patient's own β-blocker medication, propranolol, had a marginal effect on APD in the LQTS-hiPSC-CMs. However, APD could be significantly reduced by up to 19% with compounds that enhanced the IKr current by direct channel binding or by indirect mediation through the PPARδ/protein 14-3-3 epsilon/HERG pathway. Drug-induced enhancement of an alternative potassium current, IKATP, also reduced APD by up to 21%. This study demonstrates the utility of LQTS-hiPSC-CMs in evaluating whether drugs can shorten APD and, importantly, shows that PPARδ agonists may form a new class of therapeutics for this condition.